Towards a national puppet centre for the Lebanon - Knio, Mona (1994)
The impression that Arabs did not attempt to express themselves through the medium of dramatic arts till recently echoes a simultaneous conviction which prevailed concerning visual arts expression. Early in the second half of this century, researchers started questioning whether Arabs could have expressed themselves in visual or dramatic representations under the auspices of Islam. Meanwhile, we have been rediscovering our visual, oral and dramatic art heritage through a Western cultural perspective. The aim of this research is to examine the sources of inspiration which have been shaping the visual and dramatic art traditions in the Arab Middle East region over the past five thousand years. Little attention has been given to the interplay between the various forms of artistic expression in the Middle East. Besides, much less concern has been articulated about the performance arts interpretation of the notion of abstraction which characterises the artistic expressions of the region. One performance art form that has gone a long way in the direction towards abstraction is puppetry. From the times of the Pharaohs and Mesopotamians, puppets and masked actors communicated myths and legends in religious rituals and festivals. Later, puppets continued under Islam to communicate secular themes and narratives. Puppets, by their nature, involve the concept of alienation and enable the modern Arab to present ideas in a manner consistent with his intellectual, cultural and aesthetic predilections. In its search for forms of dramatic expression the Lebanese theatre might profitably look into its own cultural heritage, try to learn from and experiment with the various types of oral and performance traditions especially puppetry which has been long forgotten.